Impact of drip irrigation and boron application on seed yield, yield components, and water use efficiency of alfalfa in Northwest China - Dali Chen; Jinglong Bao; Tao Chen; Dongfeng Ma; Jia Pan; Mengjie Bai; Yanrong Wang; Zhibiao Nan; Xiaowen Hu (Journal of Agriculture and Food Research)
Enhancing alfalfa seed yield is essential for its comprehensive utilization in the forage, ecological, energy, and food sectors. Optimal irrigation and nutrient management are widely acknowledged as key factors in the arid and semiarid regions. However, the synergistic effects of drip irrigation and micronutrient application, particularly boron, on alfalfa seed production in these areas remain insufficiently understood. To address this gap, we conducted a three-year field experiment to investigate the impact of four irrigation frequencies (2, 3, 4, and 5 times, with 50 mm per application) and four boron concentrations (0, 0.3 %, 0.6 % and 0.9 %) on seed yield, water use efficiency (WUE), and economic benefits in alfalfa. Our results revealed a negative parabolic relationship between seed yield and both irrigation amount and boron concentration. The highest seed yields were achieved with three irrigations (150 mm) combined with a 0.6 % boron application, except for the year of 2021. In 2022and 2023, this optimal treatment resulted in seed yields of 931.28 kg/hm2 and 983.98 kg/hm2, representing a 3.22-fold and 2.08-fold increase compared to the control, respectively. This treatment also produced the highest WUE, with an average value of 2.31 kg/hm2/mm from 2021 to 2023, reflecting a 2.92-fold increase over the control. Furthermore, seed yield exhibited a strong positive correlation with all key yield components (P < 0.001). The structural equation model identified the number of reproductive branches per plant as the most significant contributor to seed yield. These findings provide valuable insights into the effects of irrigation and boron application on alfalfa seed yield and offer practical guidance for optimizing agronomic practices aimed at improving seed production in alfalfa and similar crops.